Heroism, Celebrity and Therapy in Nurse Jackie - Pullen, Christopher; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
This book presents an examination of the television series Nurse Jackie, making connections between the representational processes and the audience consumption of the series. A key point of reference is the political and performative potential of Nurse Jackie with regards to its progressive representation of prescription drug addiction and its relationship to the concept of quality television. It deconstructs Nurse Jackie$1 (Bs discursive potential, involving intersections with contemporary notions of genre, celebrity, self-reflexivity, therapy and feminisms
Introduction -- 1. Female Work and Hospital Drama -- 2. American Dream and The Absent Mother -- 3. Edie Falco and Star Persona -- 4. The Heroine and Morality -- 5. Therapy and Institution -- Conclusion: A Call to Action.
Includes bibliographical references and index.
Also available in print format.
Keywords: PERFORMING ARTS / Television / General; SOCIAL SCIENCE / Gender Studies; Television programs -- United States -- Criticism and interpretation; Television programs; Electronic books